(untitled) (Medical Forum Monthly, 2024)
Objective: The study aimed at assessing the knowledge of health care providers and identifying the factors affecting knowledge about safe injection practices. Study Design: A cross sectional study. Place and Duration of Study: This study was carried out at Gujar Khan, District Rawalpindi from July, 2011- October, 2011. Materials and Methods: 37 health care facilities (72.7% private and 27.3% public) were selected conveniently. 110 Health Care Providers (HCP’s) were selected on the basis of availability. HCP’s who were involved in clinical work for more than six months were included. Permission was obtained from ethical committee of Health Services Academy and the owners of the health care facilities. The knowledge of the HCPs was assessed through specifically developed scoring scheme and was categorized into good, fair and poor, while the factors affecting knowledge were assessed by applying Chi-square tests. .(p≤0.05). Results: 70% of the HCPs had fair, 20.1% had poor and only 9.1% had good knowledge. Good knowledge was seen in doctors and graduate nurses. Poor knowledge was observed in non-certified HCP’s. 57.3% had never heard about the use of Personal protective equipment (PPE), 93.6% heard of the availability of vaccination for HBV and 58.2% of them were vaccinated against HBV. 57.3% had never heard of safe injection policy guidelines. 55.5% HCPs had ever received any needle prick injuries. Cadre (p=0.000) and professional education/training in medicine (p=0.002) were significant factors. Conclusion: The overall knowledge of the HCPs was above average, non certified HCP’s had poor knowledge. Cadre (p= 0.000) and Professional education/trainings (p=0.002) were significant factors affecting knowledge.